2017
DOI: 10.1021/acsami.7b14096
|View full text |Cite
|
Sign up to set email alerts
|

Porous NiFe-Oxide Nanocubes as Bifunctional Electrocatalysts for Efficient Water-Splitting

Abstract: Electrocatalytic water-splitting, a combination of oxygen and hydrogen evolution reactions (OER and HER), is highly attractive in clean energy technologies, especially for high-purity hydrogen production, whereas developing stable, earth-abundant, bifunctional catalysts has continued to pose major challenges. Herein, a mesoporous NiFe-oxide nanocube (NiFe-NC) system is developed from a NiFe Prussian blue analog metal-organic framework as an efficient bifunctional catalyst for overall water-splitting. The NiFe-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
149
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(161 citation statements)
references
References 62 publications
11
149
1
Order By: Relevance
“…Linear sweep voltammetry (LSV) measurements were carried out with 95 % iR ‐compensations at 1 mV s −1 . The linear portions of the Tafel plots were derived from the LSV curves according to the Tafel equation: η = b log ( j )+a, where j represents the current density and b is the Tafel slope . The ECSA of electrodes were estimated by double layer capacitance measurements .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Linear sweep voltammetry (LSV) measurements were carried out with 95 % iR ‐compensations at 1 mV s −1 . The linear portions of the Tafel plots were derived from the LSV curves according to the Tafel equation: η = b log ( j )+a, where j represents the current density and b is the Tafel slope . The ECSA of electrodes were estimated by double layer capacitance measurements .…”
Section: Methodsmentioning
confidence: 99%
“…The linear portions of the Tafel plots were derived from the LSV curves according to the Tafel equation: η = blog (j) + a, where j represents the current density and b is the Tafel slope. [13] The ECSA of electrodes were estimated by double layer capacitance measurements. [31] To measure electrochemical capacitance, a series of CVs were performed across À 0.05 V~0.05 V of the open-circuit potential at scan rates of 5, 10, 25, 50, 100 and 200 mV s À 1 .…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Bhattacharyya et al. reported mesoporous NiFe‐oxide nanocubes as an efficient material for overall water‐splitting . The method follows a crystallization process of 7 days to form NiFe Prussian blue analog crystal which was further calcined to form NiFe 2 O 4 nanocubes.…”
Section: Introductionmentioning
confidence: 99%
“…[53] Likewise, Bhattacharyya et al reported mesoporous NiFe-oxide nanocubes as an efficient material for overall water-splitting. [54] The method follows a crystallization process of 7 days to form NiFe Prussian blue analog crystal which was further calcined to form NiFe 2 O 4 nanocubes. The nanocubes demonstrated excellent activity with overpotentials of 271 and 197 mV for OER and HER, respectively, in 1 M KOH at 10 mA cm À 2 .…”
Section: Introductionmentioning
confidence: 99%